1997
DOI: 10.3109/00016489709124014
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Electrocochleography: Instrumentation Settings and Meta-analysis of Criteria for Diagnosis of Endolymphatic Hydrops

Abstract: This paper reviews the literature on instrumentation settings used for transtympanic (TT-ECOG) and extratympanic electrocochleography ( ET-ECOG). There is wide variation with regard to the applied stimulus, the settings and interpretation of ECOG results. For most physicians, the presence of endolymphatic hydrops is indicated either by the summating/action potential (SP/AP) ratio for click stimuli or the SP amplitude after tone bursts. Different upper limits have been proposed to discriminate hydropic from non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 44 publications
2
17
1
2
Order By: Relevance
“…In this study, ECoG results were not well correlated with audiometric data and the side of disease for patients with definite and probable Ménière’s disease with unilateral low-frequency loss. This finding was consistent with previous reports [4, 8, 9]. In addition, we also showed that the SP/AP ratio was not affected significantly by sex or age (by multivariate linear regression analysis).…”
Section: Discussionsupporting
confidence: 83%
“…In this study, ECoG results were not well correlated with audiometric data and the side of disease for patients with definite and probable Ménière’s disease with unilateral low-frequency loss. This finding was consistent with previous reports [4, 8, 9]. In addition, we also showed that the SP/AP ratio was not affected significantly by sex or age (by multivariate linear regression analysis).…”
Section: Discussionsupporting
confidence: 83%
“…This diagnostic criterion was obtained from a meta-analysis performed by Wuyts et al [1997]. This analysis showed that, based on the results of 9 TT-ECoG studies, an SP/AP ratio of 0.35 was able to discriminate normal individuals from MD patients.…”
Section: Methodsmentioning
confidence: 99%
“…The test was performed and interpreted following the test protocol that was published by Wuyts et al [1997Wuyts et al [ , 2001. After the ipsilateral mastoid and the forehead were cleansed with alcohol-soaked wipes, electrode gel was applied to reduce impedance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Die se Er wei te rung des End olym ph rau mes, die auf eine Re gu la ti onsstö rung der In ne nohr flüs sig kei ten zu rück-zu füh ren ist [14], hat eine Be we gungs einschrän kung der Ba si lar mem bran zur Folge. Bis her wird v. a. die Elek tro koch leo graphie [3,20] ein ge setzt, um auf eine Funkti ons stö rung des Cor ti-Or gans beim EH zu schlie ßen.…”
unclassified